The Influence Of Medical Officer Knowledge And Facilities Of Medical Recording Documents On Inaccuracies Of Main Diagnosis Codes According To Icd-10 In Medical Record Documents At dr. Soepraoen Hospitals Malang - Anis Ansyori; Fita Rusidan Ikawati; Ahmad Jaelani (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2021)
The competence of a medical recorder is to code diagnosis. But in the fact, there are still many medical officers who experience some difficulties in coding diagnoses quickly, precisely, and accurately. This study is here to find out the effect of the knowledge of medical personnel and medical record document facilities on the inaccuracy of the main diagnosis code according to ICD-10 in the medical record document at dr. Soepraoen Malang. This research uses a qualitative method with a case study approach design. The location of this research is DR. Soepraoen Hospital, Malang. Processing data in this study is use non statistic. The result of this study is there is a negative and significant effect of health workers knowledge partially on the inaccuracies of main diagnosis codes, there is a negative and significant effect of hospital facilities partially on the inaccuracies of main diagnosis codes, there is a simultaneous negative and significant effect of health workers knowledge and hospital facilities on the inaccuracies of main diagnosis codes.